Food nutrition program reporting system - Boggavarapu, Sravya (Kansas State University, 2012)
FNPRS program offers nutrition education all over the counties in Kansas. It is necessary to keep track of the budget expenses for the program, resources used and many other parameters involved in the program. There exist number of commodities and products in the process of educating people. Research is needed to determine which value-added products or processes are economically possible and what percentage of it is accepted by people. For these issues, it is very important to maintain this information in a database and generate reports accordingly. The aim of the project is to create a web interface for users to enter the program information regarding the various programs conducted by Family Nutrition Program. The various kinds of data include information about the budget for the program, information about the various collaborating agencies, various kinds of resources used, services provided, proposed equipment and travel funds etc. Users for this application are county agents who take the responsibility of conducting the program and managing their data. Creating a web interface provides a solution to facilitate the agents to manage their data more efficiently and to monitor their records on a day to day basis. It also aims for generating reports for Family Nutrition Program in order to keep a check over their advancements in the program. This project involves handling of various kinds of information such as FNP Proposals, Agent information, FNP Funds, Collaborating Agencies. Database maintenance is made simple thereby allowing the administrators to add as much as data possible and manage accordingly.
Keywords: Food Nutrition Program; ASP.Net; Nutrition; Reporting system; Nutrition (0570); Web Studies (0646)